Wrestling: An Integral Part of Iranian Fighting Arts - Khorasani, Manouchehr Moshtagh (Revista de Artes Marciales Asiáticas, 2012)
Wrestling played and has been playing a very important role in Iranian cultural heritage. First, the present article discusses the terms and different uses of wrestling techniques be it in unarmed duels or in combination with weapons. Then, three relevant manuscripts will be analyzed such as an untitled wrestling manuscript by an anonymous author from the period of Sah Esmail Safavid (1502-1524 C.E.), the manuscript Tumar-e Purya-ye Vali also written by an anonymous author during the Safavid period (1502-1722 C.E.) and the work by a famous poet named Mirnejat with the title Masnavi-ye Golkosti-ye Mirnejat that was written towards the end of the period of Sah Soleyman Safavid (1666-1694 C.E.) or the beginning of the period of Sah Soltan Hosseyn Safavid (1694-1722 C.E.). Based on some terms and descriptions of the techniques found in these manuscripts, it is possible to appreciate how traditional forms of wrestling in Iran have preserved some of these techniques.